Skin Biophysical Characteristics in Patients with Keratoconus: A Controlled Study - Reza M. Robati; Bahram Einollahi; Hoda Einollahi; Shima Younespour; Shahed Fadaifard (Scientifica)
Background. Keratoconus is a relatively common corneal disease causing significant visual disability. Individuals with connective tissue disorders that affect the skin such as Marfan’s syndrome and Ehlers-Danlos syndrome or patients with atopic dermatitis show an increased prevalence of keratoconus. It seems that there are some concurrent alterations of skin and cornea in patients with keratoconus. Objective. We plan to compare skin biophysical characteristics in patients with keratoconus and healthy controls. Methods. Forty patients with keratoconus (18 females and 22 males) with mean (SD) age of 33.32 (9.55) years (range 19–56) and 40 healthy controls were recruited to this study. Skin biophysical characteristics including cutaneous resonance running time (CRRT), stratum corneum hydration, and melanin values were measured in patients and controls. Results. The median CRRT, stratum corneum hydration, and melanin measurements were significantly lower in patients with keratoconus in comparison with healthy controls. Conclusion. There are some alterations of skin biophysical properties in patients with keratoconus. Therefore, the assessment of these skin parameters could provide us some clues to the possible common biophysical variations of cornea and skin tissue in diseases such as keratoconus.